Prevalence and incidence of keratoconus in Sweden. A nationwide register study between 2010 and 2020. - Binder, Jonathan; Sundling, Vibeke (Scandinavian Journal of Optometry and Visual Science, 2023)
The purpose of this study was to estimate the prevalence and incidence of keratoconus in Sweden. The study had a cross-sectional descriptive design, using data from the Swedish Patient Register. Data about keratoconus registered from 1st January, 2010, to 31st December, 2020, were analysed. Prevalence was estimated from the total number of patients registered. Incidence was estimated from the number of first-time registrations per year for the age group 0 to 40 years and stratified by decades of age. From 2010 to 2020, 16,055 patients were registered with keratoconus in the Swedish Patient Register, giving a total estimated keratoconus prevalence of 169.5 per 100,000 (95% CI: 144.9–194.1), 74.2% were male. The estimated annual incidence of keratoconus was 11.8 per 100,000 (95% CI: 5.1–18.5). The average annual incidence was highest in the decade 21 to 30 years, 26.1 per 100,000 (95% CI: 16.1–36.1). For the age group 0 to 40 years, the estimated incidence of keratoconus was 22.5 per 100,000 (95% CI: 13.7–32.3). Keratoconus should not be regarded as an uncommon condition. The prevalence of keratoconus may be even higher because of under-registration among older citizens. The estimated prevalence and incidence of keratoconus in Sweden is comparable to estimated prevalence in Norway.